An Elongator mouse model of ALS spotlights TDP-43 in the motor neuron nucleolus - Magge Snow; BreAnna Cameron; Renzie Pond; Rachel Trudell; Sara Snyder; Lauryn Torres-Hernandez; Devyn Deschamps; Danara Tulimaiau; Kiana Hawkinson; Morgan Russell; Danielle Horan; Joseph Walters; et al. (Communications Biology)
Abstract Dysfunction of Elongator is associated with amyotrophic lateral sclerosis (ALS). Here, we describe mouse models in which either Elongator subunit 1(Elp1) or subunit 3 (Elp3) is selectively ablated in alpha motor neurons of the spinal cord. These mice exhibit a progressive loss of motor strength and motor neuron degeneration. To interrogate the molecular mechanisms that contribute to motor neuron cell death in these mice, we examine multiple disease pathways, including the expression of TDP-43 whose cytoplasmic aggregation is associated with the human disease. Although TDP-43 is a well-characterized nuclear protein functioning in RNA metabolism and gene transcription, here we document TDP-43’s robust presence in the nucleolus of wild-type motor neurons and its clearance from both the nucleus and the nucleolus of motor neurons in Elp conditional knockout mice. Thus, this study directly links dysfunction of Elongator with nucleolar disruption and TDP-43 clearing, two hallmark cellular pathologies of ALS.